Multiple methods of assessing nectar foraging conditions indicate peak foraging difficulty in late season. Issue 6 (23rd May 2020) - Garbuzov, Mihail; Balfour, Nicholas J.; Shackleton, Kyle; Al Toufailia, Hasan; Scandian, Luciano; Ratnieks, Francis L. W.
Abstract: One of the major challenges faced by pollinators worldwide is the reduction in their food supply, nectar, and pollen. Given the considerable seasonal variation in the abundance of both floral resources and flower‐visiting insects, conservation initiatives aiming to help pollinators through floral resource supplementation could increase their impacts by targeting periods when the foraging conditions are most difficult. Direct assessment of foraging conditions, however, is extremely labour‐intensive. Here, we compared eight practical measures expected to reflect the foraging difficulty for nectar in the environment. Five measures involved Apis mellifera – an indicator species for the flower‐visitor guild due to its generalist, energetically optimal, and long‐distance foraging habit. These included (i) visitation at feeders with a range of sucrose concentrations, (ii) guarding and (iii) fighting levels at hive entrances, (iv) rates of hive weight changes, and (v) foraging distances encoded in waggle dances. The other measures were (vi–viii) counts of flower‐visiting insects in relation to the rate of nectar sugar secretion in three plant species attractive to flower‐visiting insects. There was considerable, although not complete agreement among the eight measures. Eleven of 28 pairwise correlations were statistically significant. Guarding and fighting correlated with most (five) other measures. We conclude that seven of the eight measures could be potentially useful in gauging seasonal patterns in local foraging conditions, which could help guide targeted conservation initiatives. Assessment of guarding and fighting levels at A. mellifera hive entrances is recommended, as these correlated significantly with most other measures and are easy to obtain in practice. Abstract : Knowledge of how foraging conditions vary seasonally could help in design of effective food supplementation initiatives aimed at conserving pollinators. We examined eight potential proxy variables that could be used to gauge foraging difficulty for nectar in the environment, seven of which had considerable agreement among each other. Guarding and fighting levels at honey bee hive entrances are recommended, as they correlated with most other variables and are among the least difficult to obtain.